The inhibitory effects of phenolic and terpenoid compounds from Baccharis trimera in siha cells : differences in their activity and mechanism of action - Oliveira, Cristiane Bernardes de (2013)
Baccharis trimera is used in folk medicine as a tea for digestive and liver diseases. It possesses anti-inflammatory and antioxidant properties that are related to the presence of phenolic compounds. The aim of this work was to investigate the anti-proliferative properties of phenolic (PHE) and terpenoid (SAP) compounds from B. trimera on human cervical cancer. The treatment of SiHa cells with PHE for 24 h suppressed colony formation in a dose-dependent manner, inhibited proliferation and inhibited cell motility. Although SAP inhibited the proliferation of SiHa cells in a dose-dependent manner, it increased colony formation and did not inhibit cell motility. PHE and SAP also promoted a significant increase in lactate dehydrogenase levels in the culture medium in a dose-dependent manner, indicating a loss of cell membrane integrity. Moreover, PHE promoted necrotic cell death, whereas SAP induced apoptosis. These compounds are new anticancer prototypes due their significant anticancer activity demonstrated herein.